Study Explanatory and Confirmatory of People Strong In Faith Bearing The Weak Based on Roma 15:1-4 For SMP 3 BOPKRI Yogyakarta - Roseta, Roseta; Uriptiningsih, Ana Lestari; Parulian, Tamba (Basilius Eirene Press, 2023)
The problem that often occurs is the life of Christians who do not care about people who are weak in faith. This reality is a life that deviates from the teachings in the Bible. The purpose of this study is to explain and confirm people who are strong in faith supporting the weak at SMP BOPKRI 3 Yogyakarta. The method used in this research is quantitative using a questionnaire to confirm 66 people. The results of the study found that the dimension of strong people bearing the weak is the dominant dimension in determining the explanatory and confirmatory life glorifying God. This is proven through testing with linear regression analysis, which results that strong people bear weak people have an influence of 0.944 and the highest contribution for students at SMP BOPKRI 3 Yogyakarta class VIII is 94.4%.